Promising Plum Cultivars and Selection from the Ukrainian Breeding Program - Kishchak, Olena; Filyov, Volodymyr; Laskavy, Victor (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The authors present the research results of new plum cultivars and promising selections (Prunus domestica L.), bred at the L.P. Symyrenko research pomology station of the Institute of Horticulture NAAS of Ukraine, under the conditions of the Ukrainian Western Forest-Steppe in order to select the most promising in the relation of economic-valuable traits. Field, laboratory, comparative research methods have been applied as well as statistical ones. The cultivars with compact crown habit and high unit yield capacity, in particular Oda, Nenka, selection № 8087 (Aria), which crown volume have never exceed 20 m3 and the unit productivity was 2.0–2.5 kg/m3, were distinguished. In addition to these, high yield capacity per area unit had such varieties as Originalna, Prestige and selection № 8121 (Yantarna Mlyivska). It was established that their fruits are characterized by a high average mass (41.4–58.3 g), high flavor properties (8.4–8.5 points) and can be used in commercial orchards of Ukraine. Тhus, among the studied varieties there were determined the best according to the complex of valuable economic features: in early ripening group – Nenka and Oda, the middle ripening – elite selections No. 8087 (Aria), No. 12456 (Dobra), No. 8121 (Yantarna Mlyievska), and the late-ripening ones Originalna and Prestige, which can be widely used in commercial orchards of Ukraine for significantly increase of yields and profitability.